Opening sessions (OS): A tool to facilitate bioinformatic digestion in dry-laboratory exercises - L. Castro-Mejía, Josue (Improving University Science Teaching and Learning, 2023)
Finding alternatives techniques to facilitate digestion and consolidation of knowledge derived from distinct scientific disciplines is an important task of interdisciplinary teaching. During a master course that enrolled 63 individuals, we aimed at evaluating the integration of opening teaching sessions (OS) and their impact on formative assessment and student satisfaction. Integration of OS significantly increased the acquisition and usage of elementary bioinformatic concepts/skills, which was evaluated throughout inquiries for formative teaching. Furthermore, application OS corresponded with a high level of satisfaction possibly by driving instructional effectiveness and student centeredness.